O município de Porto Murtinho/MS e a Rota Bioceânica: uma análise da leitura comunitária do Plano Diretor Municipal - Ferreira, Marcia Aparecida de Castro Burgedurf (2024)
The elaboration of a Municipal Master Plan is an essential instrument for the planning of the territory. In this context, the municipality of Porto Murtinho/MS (Brazil) seeks the elaboration of this instrument at a time of great expectation of local development, with the implementation and operationalization of the Bioceanic Route. Seeking to understand all these dynamics, this research analyzes, through bibliographical and documental investigation as well as statistical analysis, the population's perspective on local development and the (re)organization of the territory with the implementation of the Bioceânica Route, based on some theoretical bases-conceptual encompassed by geographic science. The research analysis was based on relating the opinion of the population about the enterprise and the economic and social growth in the municipality, visualizing everyone's expectations and the interaction between the border cities of Porto Murtinho/MS and Carmelo Peralta/Paraguay, positive population participation and assisting managers in the elaboration of the Municipal Master Plan. The research indicated that almost all of the inhabitants interviewed have a perspective of positive impacts for the municipality with the implementation of the Bioceânica Route, however, they demand greater participation in planning and local decision-making.